Generalized immune activation as a direct result of activated CD4+ T cell killing - Kioussis Dimitris (Journal of Biology, 2009)
Abstract Background In addition to progressive CD4+ T cell immune deficiency, HIV infection is characterized by generalized immune activation, thought to arise from increased microbial exposure resulting from diminishing immunity. Results Here we report that, in a virus-free mouse model, conditional ablation of activated CD4+ T cells, the targets of immunodeficiency viruses, accelerates their turnover and produces CD4+ T cell immune deficiency. More importantly, activated CD4+ T cell killing also results in generalized immune activation, which is attributable to regulatory CD4+ T cell insufficiency and preventable by regulatory CD4+ T cell reconstitution. Immune activation in this model develops independently of microbial exposure. Furthermore, microbial translocation in mice with conditional disruption of intestinal epithelial integrity affects myeloid but not T cell homeostasis. Conclusions Although neither ablation of activated CD4+ T cells nor disruption of intestinal epithelial integrity in mice fully reproduces every aspect of HIV-associated immune dysfunction in humans, ablation of activated CD4+ T cells, but not disruption of intestinal epithelial integrity, approximates the two key immune alterations in HIV infection: CD4+ T cell immune deficiency and generalized immune activation. We therefore propose activated CD4+ T cell killing as a common etiology for both immune deficiency and activation in HIV infection. See minireview http://www.jbiol.com/content/8/10/91